Pengembangan Evaluasi Pembelajaran Pendidikan Agama Islam Berbasis Kurikulum Merdeka di Madrasah Ibtidaiyah - Khoirul Imam; Arfan Hamdani; Achmad Rasyid Ridha (TSAQOFAH, 2026)
The evaluation of Islamic Religious Education (PAI) learning within the Kurikulum Merdeka emphasizes holistic, authentic, and student-centered assessment, but its implementation in Madrasah Ibtidaiyah still faces various challenges. This study aims to describe and analyze the development of PAI learning evaluation based on the Kurikulum Merdeka in Madrasah Ibtidaiyah. This study employed a qualitative approach using a literature review method. The data were analyzed descriptively to identify the forms of evaluation, assessment instruments, scope of competencies, and implementation constraints. The results showed that PAI learning evaluation comprised diagnostic, formative, and summative assessments integrated with authentic assessment. Evaluation instruments were developed in the form of written tests, observations, religious practice assessments, portfolios, and religious projects. The evaluation measured not only cognitive abilities but also affective and psychomotor domains that reflected the internalization of Islamic values. However, its implementation still faced limitations in teacher competence, difficulties in assessing attitudes, and time constraints. This study concludes that the development of evaluation based on the Kurikulum Merdeka has a positive impact on the quality of PAI learning and the formation of students’ religious character. The implications of this study emphasize the importance of improving teacher competence, utilizing technology, and strengthening collaboration with parents to support the implementation of comprehensive and sustainable PAI learning evaluation.